Information System for Deciding the Route to Transport Goods Between Bangkok and Mukdahan Province in Thailand - Akharadet, N.; Prapai, S.; Piyanan, I. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The objective of this research is to develop an information system for deciding the route to transport goods between Bangkok and Mukdahan province in Thailand. Many techniques are used in this system, such as the risk analysis, analytic hierarchy process and zero-one goal programming. This system is tested by 50 customers from a shipping company in Bangkok, Thailand. The results showed that the system offers shipping cars for customers, and reduces time and errors in finding the transportation routing from staff. Furthermore, the system decreases the time of transaction documents and reduces the time to decide from customer. Staff have not over skill but they can use this program. This research surveys satisfaction of 50 customers. This survey finds the average score of satisfaction is 4.67 from 5. In addition, the number of customers increases by 25.37 percent.